Insight into the Final Step of the Supramolecular Buildup of Eumelanin - Büngeler, Anne; Hämisch, Benjamin; Huber, Klaus; Bremser, Wolfgang; Strube, Oliver I. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Fluid Flow Programming in Paper-Derived Silica-Polymer Hybrids - Dubois, C.; Herzog, N.; Ruettiger, C.; Geissler, A.; Grange, E.; Kunz, U.; Kleebe, H. J.; Biesalski, M.; Meckel, T.; Gutmann, Torsten; Gallei, M.; Andrieu-Brunsen, A. (Langmuir)
In paper-based devices, capillary fluid flow is based on length-scale selective functional control within a hierarchical porous system. The fluid flow can be tuned by altering the paper preparation process, which controls parameters such as the paper grammage. Interestingly, the fiber morphology and nanoporosity are often neglected. In this work, porous voids are incorporated into paper by the combination of dense or mesoporous ceramic silica coatings with hierarchically porous cotton linter paper. Varying the silica coating leads to significant changes in the fluid flow characteristics, up to the complete water exclusion without any further fiber surface hydrophobization, providing new approaches to control fluid flow. Additionally, functionalization with redox-responsive polymers leads to reversible, dynamic gating of fluid flow in these hybrid paper materials, demonstrating the potential of length scale specific, dynamic, and external transport control.

Self-Assembly, Dynamics, and Polymorphism of hIAPP(20–29) Aggregates at Solid–Liquid Interfaces - Hajiraissi, Roozbeh; Giner, Ignacio; Grundmeier, Guido; Keller, Adrian (Langmuir)

Temperature-Dependent Charge Transport through Individually Contacted DNA Origami-Based Au Nanowires. - Teschome, B; Facsko, S; Schönherr, T; Kerbusch, J; Keller, Adrian; Erbe, A (Langmuir)

Structure of n-Alkyltrichlorosilane Monolayers on Si(100)/SiO2 - Steinrück, Hans-Georg; Will, J.; Magerl, A.; Ocko, B. M. (Langmuir)

Alignment of Gold Nanoparticle-Decorated DNA Origami Nanotubes: Substrate Prepatterning versus Molecular Combing - Teschome, Bezu; Facsko, Stefan; Gothelf, Kurt V.; Keller, Adrian (Langmuir)

Gelled Lyotropic Liquid Crystals - Xu, Yang; Laupheimer, Michaela; Preisig, Natalie; Sottmann, Thomas; Schmidt, Claudia; Stubenrauch, Cosima (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Simulation of Capillary Bridges between Nanoscale Particles - Dörmann, Michael; Schmid, Hans-Joachim (Langmuir)
Capillary forces are very important as they exceed in general other adhesion forces. But at the same time the exact calculation of these forces is very complex, so often assumptions and approximations are used. Previous research was done with regard to micrometer sized particles, but the behavior of nanoscale particles is different. Hence, the results for micrometer sized particles cannot be directly transferred when considering nanoscale particles. Therefore, a simulation method was developed to calculate numerically the shape of a rotationally symmetrical capillary bridge between two spherical particles or a particle and a plate. The capillary bridge in the gap between the particles is formed due to capillary condensation and is in thermodynamic equilibrium with the gas phase. Hence the Kelvin equation and the Young–Laplace equation can be used to calculate the profile of the capillary bridge, depending on the relative humidity of the surrounding air. The bridge profile consists of several elements that are determined consecutively and interpolated linearly. After the shape is determined, the volume and force, divided into capillary pressure force and surface tension force, can be calculated. The validation of this numerical model will be shown by comparison with several different analytical calculations for micrometer-sized particles. Furthermore, it is demonstrated that two often used approximations, (1) the toroidal approximation and (2) the use of an effective radius, cannot be used for nanoscale particles without remarkable mistake. It will be discussed how the capillary force and its components depend on different parameters, like particle size, relative humidity, contact angle, and distance, respectively. The rupture of a capillary bridge due to particle separation will also be presented.

Use of Eutectic Mixtures for Preparation of Monolithic Carbons with CO2-Adsorption and Gas-Separation Capabilities - Lopez Salas, Nieves; Jardim, E. O.; Silvestre-Albero, A.; Gutiérrez, M. C.; Ferrer, M. L.; Rodríguez-Reinoso, F.; Silvestre-Albero, J.; del Monte, F. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Mechanistic Studies of Silica Polymerization from Supersaturated Aqueous Solutions by Means of Time-Resolved Light Scattering - Kley, M.; Kempter, A.; Boyko, V.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Mechanistic Studies of Silica Polymerization from Supersaturated Aqueous Solutions by Means of Time-Resolved Light Scattering - Kley, Marina; Kempter, A.; Boyko, V.; Huber, Klaus (Langmuir)

Structural Evolution in the Isotropic Channel of a Water–Nonionic Surfactant System That Has a Disconnected Lamellar Phase: A 1H NMR Self-Diffusion Study - Stubenrauch, Cosima; Kleinschmidt, Felix; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Impact of Sodium Polyacrylate on the Amorphous Calcium Carbonate Formation from Supersaturated Solution - Liu, J.; Pancera, S.; Boyko, V.; Gummel, J.; Nayuk, R.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Molecular Recognition with 2,4-Diaminotriazine-Functionalized Colloids - Bayer, Frank M.; Tang, Mingxue; Michels, Rolf; Schmidt, Claudia; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Molecular Recognition with 2,4-Diaminotriazine-Functionalized Colloids - Bayer, Frank M.; Tang, Mingxue; Michels, Rolf; Schmidt, Claudia; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Size Determination of Shear-Induced Multilamellar Vesicles by Rheo-NMR Spectroscopy - Medronho, B.; Schmidt, Claudia; Olsson, U.; Miguel, M. G. (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced Defect Formation in a Nonionic Lamellar Phase - Medronho, B.; Rodrigues, M.; Miguel, M. G.; Olsson, U.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Evaluation of the Particle Growth of Amorphous Calcium Carbonate in Water by Means of the Porod Invariant from SAXS - Liu, J.; Pancera, S.; Boyko, V.; Shukla, A.; Narayanan, T.; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Hydrogen-Bond-Induced Heteroassembly in Binary Colloidal Systems - Bayer, Frank M.; Hiltrop, Karl; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Shear-Induced Transitions between a Planar Lamellar Phase and Multilamellar Vesicles: Continuous versus Discontinuous Transformation - Medronho, B.; Shafaei, S.; Szopko, R.; Miguel, M. G.; Olsson, U.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science